Rancang Bangun Chatbot Reservasi Kelas Kursus Pada Stephen Komputer Jambi Dengan Metode Forward Chaining - FA Bambang Sukoco; Ronald Naibaho; Gunardi Gunardi (LPPM STIKOM Dinamika Bangsa, 2021)
The Helpdesk or Customer Service division in providing information and assistance that related to course services at Stephen Komputer Jambi is currently still using a conventional system, such as services by phone or in person. Likewise, the reservation system or course class registration is still adopting the same system. This conventional service will certainly take a lot of time and money for both the customer and the company, where telephone service will certainly take up time and allow queues to occur. Customer service has limitations in serving customers because it can only serve during working hours and a limited number of personnel. Chatbot is an application that designed to communicate with machines. The Chatbot application is expected to be able to replace the role of customer service to be able to respond to customers more quickly, be able to serve several customers simultaneously and not be fixated on working hours. This application was built using an expert system with the forward chaining method. The final result of this research is a chatbot application that can serve customers in terms of information, assistance and course class reservations at Stephen Computer Jambi. Keywords: Chatbot Helpdesk, Forward Chaining, botman, chatbot telegram.